Study of Pasuruan Batik with Jawi Temple Motif by UKM Sekar Wangi Sejati Cultural Anthropology Approach - Putri, Rizki Amalia (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2018)
Studying culture is endless because each culture will change along with current development. Gradual change causes the function of culture has shift or it increases the function for people. A culture that has shift in function aspect is object of Jawi Temple from Pasuruan. Jawi Temple is a tourist destination. It was a part of Singhasari Kingdom. At that time, the function of the Temple was to worship then became the place for Shinghasari Kingâ€™s ash. Function shift of Jawi Temple is to become tourist object and one of object for Batik motif of Pasuruan Batik that uses local wisdom object. Function shift was studied by researcher using empirical approach with data of documentation and observation. The research problems were showing form of Jawi Temple Batik (semiotics), batik motive as function to introduce culture and history and Jawi Temple batik as cultural reflection. Cultural reflection from created motif had representation of culture and history or site in Pasuruan such as Jawi Temple, ornament motif of chrysanthemum flower, podang bird, Harmoni Building and betel leaf as icons. Representation identity through batik motif can raise tourism indirectly and become introduction of knowledge through Temple motif of Batik. People also can clearly know that batik is a representation identity in Pauruan that has many cultures.Â